2020
DOI: 10.1021/acs.jchemed.9b00815
|View full text |Cite
|
Sign up to set email alerts
|

Arrows on the Page Are Not a Good Gauge: Evidence for the Importance of Causal Mechanistic Explanations about Nucleophilic Substitution in Organic Chemistry

Abstract: This three-year study builds on prior work analyzing students' causal mechanistic explanations about acid−base reactions. Here we extend that work to characterize and investigate how students construct causal mechanistic explanations of simple nucleophilic substitution reactions. After an initial pilot study, we adopted a modified version of the original task prompt which was used in two subsequent years to compare responses from students enrolled in a transformed organic chemistry course (Organic Chemistry, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
161
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(165 citation statements)
references
References 43 publications
(131 reference statements)
3
161
1
Order By: Relevance
“…Together, these data support prior observations that while students can generally describe the role of energy in a simple, isolated system, applying that knowledge to a closely related phenomenon remains challenging (Cooper & Klymkowsky, 2013) and must be carefully scaffolded (Kararo et al, 2019;Crandell et al, 2020). Prior studies have shown that students similarly have difficulty in making spontaneous connections involving energy between disciplines (Nagel & Lindsey, 2015), and connections to biology may be particularly challenging to support given that biological phenomena are often highly contextualized (Opitz et al, 2019), as is the case here.…”
Section: Comparing Responsessupporting
confidence: 80%
“…Together, these data support prior observations that while students can generally describe the role of energy in a simple, isolated system, applying that knowledge to a closely related phenomenon remains challenging (Cooper & Klymkowsky, 2013) and must be carefully scaffolded (Kararo et al, 2019;Crandell et al, 2020). Prior studies have shown that students similarly have difficulty in making spontaneous connections involving energy between disciplines (Nagel & Lindsey, 2015), and connections to biology may be particularly challenging to support given that biological phenomena are often highly contextualized (Opitz et al, 2019), as is the case here.…”
Section: Comparing Responsessupporting
confidence: 80%
“…(2020) In 2020, the act of learning organic chemistry focused on causal mechanistic arrows in substitution reaction (Crandell et al, 2020), the application of chemical structure teaching (CST) (Zheng et al, 2020), use of card game especially in learning functional group (Bell et al, 2020), and application of Posner's approach by implementing the design-based research technique (Kaanklao & Suwathanpornkul, 2020). Furthermore, it focused on the terminal object (TOs), and the development of specific students' capabilities (Betancourt-Pérez et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Organic chemistry is a difficult course, comprises of causal mechanistic arrows used to substitute the reaction or nucleophilic attack, which is the simplest type of organic reaction (Crandell et al, 2020). Moreover, high order thinking is needed in solving the problem reaction mechanisms and chemical principles (Flynn, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…conclude that "it is a mistake to assume that students know how to approach the learning of organic chemistry because they have been successful in general chemistry". Therefore, while teaching organic chemistry, not only the content, but also learning strategies should be taught (Crandell, Lockhar, & Cooper, 2010). One possibility for guiding and therefore supporting students while learning chemistry is the use of suitable scaffolds.…”
Section: Introductionmentioning
confidence: 99%